The added value of diffusion-weighted imaging in the preoperative assessment of endometrial cancer - Gil, Rui Tiago; Cunha, Teresa Margarida; Horta, Mariana; Alves, Ines (Colégio Brasileiro de Radiologia e Diagnóstico por Imagem, 2019)
To evaluate the added value of diffusion-weighted imaging (DWI) in the preoperative assessment of myometrial invasion in endometrial cancer, in comparison with T2-weighted imaging (T2WI) and dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI).

A acurácia do estudo de difusão na avaliação pré-operatória do carcinoma do endométrio
A acurácia do estudo de difusão na avaliação pré-operatória do carcinoma do endométrio
Keywords: diffusion-weighted imaging; magnetic resonance imaging; Madeira Island; carcinoma do endométrio; endometrial cancer; Gynecology; carcinoma do endométrio; Região Autónoma da Madeira